2021
DOI: 10.3390/d13040170
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Lichens in Metrosideros excelsa in Northern New Zealand Urban Forests

Abstract: The spatial distribution of corticolous lichens on the iconic New Zealand pōhutukawa (Metrosideros excelsa) tree was investigated from a survey of urban parks and forests across the city of Auckland in the North Island of New Zealand. Lichens were identified from ten randomly selected trees at 20 sampling sites, with 10 sites classified as coastal and another 10 as inland sites. Lichen data were correlated with distance from sea, distance from major roads, distance from native forests, mean tree DBH (diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(81 reference statements)
1
1
0
Order By: Relevance
“…In agreement with [ 53 , 54 ], we found that the urban ecosystem and peri-urban areas provided a heterogeneous environment, leading to species rich community of macrolichen epiphytes.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with [ 53 , 54 ], we found that the urban ecosystem and peri-urban areas provided a heterogeneous environment, leading to species rich community of macrolichen epiphytes.…”
Section: Discussionsupporting
confidence: 91%
“…Other research found on Web of Science was out of the scope of this research. Papers focusing on indoor thermal performance [68] or forests and natural environment [69].…”
Section: Methodsmentioning
confidence: 99%
“…To check cross-correlation among the variables, the SDMToolbox 0.9 (Brown et al 2017) was used, with a Pearson correlation coefficient value of less than or equal to 0.7 set to determine the variables to include in the model (Hannah et al 2019). The variance inflation factor (VIF) of less than 7.5 determined whether multicollinearity existed in the model (Benitez et al 2021;Dormann et al 2013;ESRI 2019;González-Maya et al 2016).…”
Section: Species Distribution Modelling For Tongatapu Islandmentioning
confidence: 99%